Understanding fire growth for performance based design of bamboo structures. (March 2021) - Solarte, Angela; Numapo, Janal; Do, Tam; Bolanos, Aaron; Hidalgo, Juan P.; Torero, Jose L.
Abstract: This paper analyses the different parameters governing fire growth and presents the results obtained for laminated bamboo samples produced from the species Phyllostachys pubescens "Moso". Parameters such as critical heat flux, temperature for ignition, thermal inertia, mass loss rate and heat release rates are studied herein. Last, the ignition parameters of laminated bamboo are contrasted against the available information on bamboo and commonly used timber products. Results show that overall, laminated bamboo show higher critical heat flux for ignition, ignition temperature, and thermal inertia when compared to timber species. Highlights: Ignitability of laminated bamboo to characterise fire growth. Understanding the fundamental material behaviour to achieve a fire safe design. Results compared to commercial engineering timber products.